The structure of bow shocks formed by the interaction of pulsed-power driven magnetised plasma flows with conducting obstacles - Burdiak,GC; Lebedev,SV; Bland,SN; Clayson,T; Hare,J; Suttle,L; Suzuki-Vidal,F; Garcia,DC; Chittenden,JP; Bott-Suzuki,S; Ciardi,A; Frank,A; et al. (PHYSICS OF PLASMAS, 2017)
We present an experimental study of the development and structure of bow shocks produced by the interaction of a magnetised, collisional, super-Alfvénic plasma flow with conducting cylindrical obstacles. The plasma flow with an embedded, frozen-in magnetic field (ReM ∼ 20) is produced by the current-driven ablation of fine aluminium wires in an inverse, exploding wire array z-pinch. We show that the orientation of the embedded field with respect to the obstacles has a dramatic effect on the bow shock structure. When the field is aligned with the obstacle, a sharp bow shock is formed with a global structure that is determined simply by the fast magneto-sonic Mach number. When the field is orthogonal to the obstacle, magnetic draping occurs. This leads to the growth of a magnetic precursor and the subsequent development of a magnetised bow shock that is mediated by two-fluid effects, with an opening angle and a stand-off distance, that are both many times larger than in the parallel geometry. By changing the field orientation, we change the fluid regime and physical mechanisms that are responsible for the development of the bow shocks. MHD simulations show good agreement with the structure of well-developed bow shocks. However, collisionless, two-fluid effects will need to be included within models to accurately reproduce the development of the shock with an orthogonal B-field.